PENERAPAN METODE PEMBELAJARAN GALLERY WALK UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR DI KELAS X MIA SMAN 2 PEKANBARU - Fannia Lestari; Rini '; Elva Yasmi Amran (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The research was conducted because of the low learning achievement of student on the structure of atom and the periodic system of element who has not reached the minimum completeness criteria (KKM) was 75 that have been established in school. The research aimed to improve learning achievement of student on the structure of atom and the periodic system of element subject in X MIA class SMAN 2 Pekanbaru. This research is was kind of experimental research with Randomized Control Group Pretest-Posttest Design. The samples of the research was the student of X MIA 4 class as the experimental class and the student of X MIA 1 class as the control class which were determined randomly after doing normality test and homogenity test. The learning process of experimental class and control class used scientific approach which was based on the curriculum in 2013. Experimental class was a class that was given the treatment that used Gallery Walk learning methods while the control class was not. The data analysis technique we used was the t-test, criteria testing H0 accepted if tcount>ttable, dk = n1 + n2 – 2 with α = 0,05. Based on the result of data analysis test, we obtained tcount>ttable was 2,41>1,66, it meant that the use the application of Gallery Walk learning methods could improve learning achievement of student on the structure of atom and the periodic system of element subject in X MIA class SMAN 2 Pekanbaru.Key Words : Gallery Walk Learning, Learning Achievement, Structure of Atom and thePeriodic System of Element